The construction of collective identity in Malaysian ESL secondary classrooms - Idrus, Faizah; Mohd Nazri, Nas Idayu (Canadian Center of Science and Education, 2016)
This study seeks to identify the construction of collective identity in ESL classroom among students in a secondary school in Selangor, Malaysia. Identity construction can be helpful in supporting students academically and socially, especially in the English language classrooms. Being non-native speakers, students may have the tendency to feel isolated because of the limited knowledge in English. A qualitative investigation was employed and the samples comprised of 12 secondary students from Sekolah Menengah Kebangsaan Jeram, Kuala Selangor. In-depth interviews were carried out with the respondents.The results revealed that when constructing their personal identities, individuals may want to identify themselves with the mutual interest of the groups they are part of. Identifying oneself with a group not only means wanting to be accepted, but also adhering to having mutual identities and values of the group. Therefore, the current study seems to confirm the finding of previous studies where researchers stated that the identity of an individual is defined by its majority group with whom the individuals share the physical environment and the territory they inhabit.